Plant metabolism and biotechnology - Ashihara, Hiroshi; Crozier, Alan.; Komamine, Atsushi, 1929- (Chichester, West Sussex, U.K. : Wiley, 2011)
"Various plant metabolites are useful for human life, and the induction and reduction of these metabolites using modern biotechnical technique is of enormous potential important especially in the fields of agriculture and health. Plant Metabolism and Biotechnology describes the biosynthetic pathways of plant metabolites, their function in plants, and some applications for biotechnology. Topics covered include: Photosynthetic carbon metabolism Starch and sugar biosynthesis Cellulose (cell wall) biosynthesis Lipid biosynthesis Nitrogen fixation and assimilation Sulfur metabolism Amino acid metabolism Nucleotide metabolism Purine alkaloids Nicotine Benzylisoquinoline alkaloids (morphine, codeine) Flavonoid metabolism Pigment metabolism Use of the metabolome for biotechnology Application to biomass improvement and biodiesel Plant Metabolism and Biotechnology is an essential guide to this important field for researchers and students of biochemistry, plant biology, metabolic engineering, biotechnology, food science, agriculture, and medicine"--
"This book will describe the biosynthetic pathways of plant metabolites, their function in plants, and some applications for biotechnology such as genetic engineering to produce transgenic plants for agriculture and drug production"--
Biosynthesis and metabolism of starch and sugars / Frederik Børnke and Sophia Sonnewald -- Lipid biosynthesis / David Hildebrand -- Symbiotic nitrogen fixation / Hiroshi Kouchi -- Sulfur metabolism / Hideki Takahashi -- Nucleotide metabolism / Rita Zrenner and Hiroshi Ashihara -- Purine alkaloid metabolism / Hiroshi Ashihara, Shinjiro Ogita and Alan Crozier -- Nicotine biosynthesis / Tsubasa Shoji and Takashi Hashimoto -- Terpenoid biosynthesis / Dae-Kyun Ro -- Benzylisoquinoline alkaloid biosynthesis / Isabel Desgagni-Penix and Peter J. Facchini -- Monoterpenoid indole alkaloid biosynthesis / Vincenzo De Luca -- Flavonoid biosynthesis / Indu B. Jaganath and Alan Crozier -- Pigment biosynthesis I. Anthocyanins / Yoshihiro Ozeki [and others] -- Pigment biosynthesis II: Betacyanins and carotenoids / Masaaki Sakuta and Akemi Ohmiya -- Metabolomics in plant biotechnology / Yozo Okazaki [and others].
Includes bibliographical references and index.
Print version record.
Keywords: Plants -- Metabolism; Plant biotechnology; Natural history; Science; Chemical engineering; Botany; Engineering; SCIENCE -- Life Sciences -- Biochemistry; SCIENCE -- Biotechnology; Plant biotechnology; Plants -- Metabolism; Pflanzen; Stoffwechsel; Biosynthese; Biotechnologie; Electronic books